ОД СТАТУСА КА УГОВОРУ: БИОПОЛИТИКА МОДЕРНОГ БРАКА И ГРАНИЦЕ ДРЖАВНЕ ИНТЕРВЕНЦИЈЕ У РЕПУБЛИЦИ СРБИЈИ - Stjepanović, Bogdana M (Political Review, 2026)
The adoption of Family Law in Serbia in 2005 marks a fundamental change in how the state governs domestic life. By introducing the marriage contract, the state embraced neoliberal individualism, transferring regulatory power to private actors while maintaining institutional oversight through notary procedures. This movement functions as a biopolitical mechanism that integrates market logic into the private sphere, eroding the collective protective mechanisms characteristic of the socialist era. Despite the formal emphasis on freedom of contract, structural barriers continue to undermine equality between spouses. Moving beyond the myth of absolute autonomy, this study identifies a persistent “dilemma of choice” shaped by ideological illusions and gender-sensitive power imbalances. Through critical discourse analysis, the paper demonstrates how the neoliberal framework rebrands systemic economic risks as individual responsibilities, leaving the socio-economically weaker spouse vulnerable. The Serbian family thus remains at a critical crossroads, caught between persistent patriarchal frameworks and the atomizing pressures of globalized neoliberalism.